Venous thromboembolism compliance in a tertiary cardiothoracic centre in the UK - Ahmed Abdulelah; Malek Hassan; Alexander Davison; Sandra Mulrennan; Laura Succony; Paul Bambrough (Clinical Medicine)
Introduction: Venous thromboembolism (VTE) imposes significant national health and socioeconomic burden because of the associated morbidity and mortality. Therefore, evaluating VTE assessment compliance for patients admitted to hospital is of paramount significance to ensure that VTE events and the associated burden are minimised. Methods: Compliance in VTE assessments for patients admitted to the cardiology department at a tertiary cardiothoracic centre in the UK was reviewed for November and December 2024. Patients whose VTE assessment was not performed within 24 h of admission were flagged as non-compliant. Factors leading to the non-compliance were evaluated and analysed. Results: The overall compliance in the cardiology department in November 2024 was found to be 93.1%. 24 patients were found to have non-compliant VTE assessment. Non-compliance was most noted in admissions under the interventional cardiology team, followed by structural cardiology team and, lastly, by the electrophysiology team.Subsequently, factors leading towards non-compliance were evaluated. The most prevalent factors were weekend admissions (30.9%), late-night or overnight admissions (21.4%), unexpected admissions from day-ward or overnight stays for treat and return patients (11.9%) and non-prescribing clerking team members (38.1%).Interventions toward the identified factors were planned and introduced. These included advanced nurse practitioners performing VTE assessments for patients they clerk/admit, educational sessions regarding VTE and importance of VTE assessment to the new doctors rotating in the department or hospital, introducing a twilight shift to assist in late admissions, regular monitoring of VTE assessment status and prompt recognition of patients with incomplete VTE assessments.Accordingly, and following these interventions, the overall compliance in the cardiology department in January 2025 and February 2025 were determined to be 95.6%. The aim is to further monitor compliance and introduce interventions where needed. Conclusion: Overall, evaluating the key factors towards VTE non-compliance are of paramount significance in regard to patients’ safety and care because they enable effective introduction of interventions to tackle the resulting non-compliance.